ANALISIS KEKUATAN U-DITCH PRACETAK UNTUK MENINGKATKAN DAYA SAING PRODUK LOKAL - Titin Sundari; Fatma Ayu Nuning Farida Afiatna, (Prosiding Seminar Nasional Sains, Teknologi, Ekonomi, Pendidikan dan Keagamaan (SAINSTEKNOPAK), 2021)
U-ditch precast concrete today has been widely used in waterwork projects. This precast system has many advantages, such as the use of concrete materials and molds with certain sizes that have been adapted to the construction needs, resulting in high-strength, workability, durable and sustainable concrete. The purpose of this study is to determine the quality of local U-ditch production by identifying the existing problems so that it becomes a competitive local product. From the results of this study, it was found that local printed U-ditch products did not meet the strength requirements, for that a U-ditch + cover design proposal was given according to SNI 1725: 2016 regarding loading for bridges.